Photobiology - Kohen, Elli (Academic Press, 1995)
Photobiology integrates a wide variety of scientific disciplines. As more people become aware of the many ways light interacts with chemical and biological systems, the need for a concise treatment of photobiology has become more critical. Kohen et al. Have written just such a book, intended both as a textbook and as a reference. The authors begin by providing a brief description of the nature of light, how it affects matter, and the means and methods of measuring it. A major section of the book is devoted to how light influences living systems, including discussions of photosynthesis, bioluminescence, regulatory mechanisms, and visual transduction of light. The last half of the book is devoted to the biomedical aspects of light, including photoimmunology, photoallergic reactions and other forms of light sensitivity, the optical properties of skin, and various ways that light can be used in therapy treatments. Useful to photobiologists as a comprehensive overview, this book should also appeal to biomedical researchers and advanced students of photobiology.